New species of Peromyia from Tasmania, with a revision of Schiner’s and Skuse’s types of Australian Micromyinae (Diptera: Cecidomyiidae). - Jaschhof, Mathias (Contributions to Entomology = Beiträge zur Entomologie, 2010)
Peromyia Kieffer, 1894, a speciose, cosmopolitan genus of micromyine cecidomyiids, is shown to occur in Tasmania. This is the first record of the genus in Australia and the first contribution to the taxonomy of Australian Micromyinae for 120 years. Nine of the 12 species found proved to be new to science: Peromyia grovei sp. n., P. nitoda sp. n., P. indecorata sp. n., P. warraensis sp. n., P. bashfordi sp. n., P. despecta sp. n., P. debilis sp. n., P. cinalata sp. n., and P. tasmanica sp. n. Four of the new species are assigned to the Peromyia dissona group, which is established for a chiefly western Pacific species radiation. Other Tasmanian peromyias are assigned to species groups that to present knowledge are widely distributed accross the Holarctic Region and occasionally beyond. The types of the Micromyinae species from Australia by Ignaz R. Schiner and Frederick A. A. Skuse are revised. None of the 11 species belongs to the genus Campylomyza Meigen, 1818, where they were originally assigned. Campylomyza grandiuscula Skuse, 1890 is actually a species of the genus Pteridomyia Jaschhof, 2003. The remaining species either belong to the genus Peromyia or their generic affiliation could not be determined. Peromyia aeratipennis (Skuse, 1888) comb. n. takes priority over Peromyia muscorum (Kieffer, 1895) syn. n., and Peromyia impexa (Skuse, 1888) comb. n. takes priority over Peromyia palustris (Kieffer, 1895) syn. n. Peromyia pellax (Skuse, 1888) comb. n., syn. n. and Peromyia subtilis (Skuse, 1888) comb. n., syn. n. are identical with Peromyia impexa. Campylomyza sidneyensis Schiner, 1868, Campylomyza amplipennis Skuse, 1888, Campylomyza crocea Skuse, 1888, Campylomyza perpallida Skuse, 1888, Campylomyza persimilis Skuse, 1888, and Campylomyza vicina Skuse, 1888 are relegated to nomina dubia. Keywords Diptera, Cecidomyiidae, Micromyinae, Australasian Region, Australia, Tasmania, Peromyia, new species, new synonyms, new combinations. Nomenclatural Acts amplipennis Skuse, 1888 (Campylomyza), nomen dubium crocea Skuse, 1888 (Campylomyza), nomen dubium pellax Skuse, 1888 (Campylomyza), syn. nov. of Peromyia impexa (Skuse, 1888) perpallida Skuse, 1888 (Campylomyza), nomen dubium persimilis Skuse, 1888 (Campylomyza), nomen dubium sidneyensis Schiner, 1868 (Campylomyza), nomen dubium subtilis Skuse, 1888 (Campylomyza), syn. nov. of Peromyia impexa (Skuse, 1888) vicina Skuse, 1888 (Campylomyza), nomen dubium aeratipennis (Skuse, 1888) (Peromyia), comb. nov. hitherto Campylomyza aeratipennis Skuse, 1888 bashfordi Jaschhof, 2010 (Peromyia), spec. nov. cinalata Jaschhof, 2010 (Peromyia), spec. nov. debilis Jaschhof, 2010 (Peromyia), spec. nov. despecta Jaschhof, 2010 (Peromyia), spec. nov. grovei Jaschhof, 2010 (Peromyia), spec. nov. impexa (Skuse, 1888) (Peromyia), comb. nov. hitherto Campylomyza impexa Skuse, 1888 indecorata Jaschhof, 2010 (Peromyia), spec. nov. muscorum (Kieffer, 1895) (Peromyia), syn. nov. of Peromyia aeratipennis (Skuse, 1888) nitoda Jaschhof, 2010 (Peromyia), spec. nov. palustris (Kieffer, 1895) (Peromyia), syn. nov. of Peromyia impexa (Skuse, 1888) pellax (Skuse, 1888) (Peromyia), comb. nov. hitherto Campylomyza pellax Skuse, 1888 subtilis (Skuse, 1888) (Peromyia), comb. nov. hitherto Campylomyza subtilis Skuse, 1888 tasmanica Jaschhof, 2010 (Peromyia), spec. nov. warraensis Jaschhof, 2010 (Peromyia), spec. nov. grandiuscula (Skuse, 1890) (Pteridomyia), comb. nov. hitherto Campylomyza grandiuscula Skuse, 1890